CoH-catalyzed radical hydroalkylation of alkenes with 1, 3-dicarbonyls. Issue 34 (7th April 2022) - Guan, Meihui; Miao, Huanran; Qin, Tao; Zhang, Ge; Zhang, Qian
Abstract : A cobalt-catalyzed alkene hydroalkylation with 1, 3-dicarbonyls was developed, which is the first intermolecular version of MHAT-mediated hydrofunctionalization with C(sp 3 ) nucleophiles. Abstract : Metal-hydride hydrogen atom transfer (MHAT) catalysis has emerged as a useful reaction platform for alkene hydrofunctionalization with high chemoselectivity and predictable branched selectivity. However, MHAT-mediated hydrofunctionalization involves carbon–carbon bond formation still confined to carbon electrophiles. Here, we describe a mild, general, scalable, and functional group tolerant CoH-catalyzed intermolecular hydroalkylation of alkenes with 1, 3-dicarbonyls. This kind of CoH-catalyzed coupling of alkenes with carbon nucleophiles represents an important complement to the arsenal of MHAT-initiated hydrofunctionalization of alkenes.